ETHNIC RELATIONS AND ETHNOCENTRISM IN SELECTED MALAYSIAN SHORT STORIES - Ahmad Zufrie Abd Rahman; Ida Baizura Bahar (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2018)
The issues of the ethnic diversity of the Malaysian way of life, have been explored in scholarship on Fernando’s selection of Malaysian Short Stories (2006), consisting of six fictional narratives on life in pre-independence Malaya namely “Nannan and A Certain Cry” by Cynthia Anthony, “Ratnamuni” by K.S. Maniam, “Pasang” by Pretam Kaur, “The Third Child” by K.S. Maniam, and “Birthday” by M. Shanmugalingam, through the lens of post-colonialism. The stories have been described as an exceptional compilation due to the fact that Fernando is able to assemble stories written by authors from different ethnic backgrounds and cultures other than their own but we argue in this paper that the short stories do not contain intercultural sensitivity as they depict more ethnocentric orientations. We define ethnocentric experiences here as interculturally-sensitive elements which trigger a series of complex emotions in avoiding cultural differences either by denying their existence, raising defences against them, or by minimising their importance. Using the understanding of ethnocentrism as conceptualised by Milton J. Bennet (2013) as part of his Developmental Model of Intercultural Sensitivity, we attempt to examine the type of ethnocentric experiences depicted by the authors through selected characters in two out of the six short stories. Our findings demonstrate that the three types of ethnocentric experiences, denial, defense and minimisation of cultural differences, are indeed found embedded in the unconscious minds of the authors through their portrayals of selected characters, which in turn provide a platform of cultural fertilisation in Malaysian pluralistic society.